PEDAGOGICAL PRACTICES IN A CONTEXTUALIZED PERSPECTIVE IN THE DEVELOPMENT OF THE KNOWLEDGE FAIR AT A SCHOOL WITHIN THE PENITENTIARY SYSTEM IN RONDONÓPOLIS-MT (Editora Impacto Científico, 2025)
This article reports on experiences regarding pedagogical practices within a contextualized perspective in the construction of the knowledge fair: "Raising Awareness to Preserve," developed by teachers at the Nova Chance State School - Annex Classrooms to the Major Eldo Sá Correa Penitentiary "Mata Grande," in Rondonópolis-MT, in the 1st and 2nd Segments of Elementary School, High School - Youth and Adult Education - EJA for People Deprived of Liberty - PPL, and the "Zumbi dos Palmares - PPL" Preparatory Course during the 2019 school year. The objective was to improve students' knowledge about topics involving the conservation of water, soil, and rivers, enabling the development of attitudes for preservation and sustainable development. To this end, we conducted transdisciplinary classes, debates, and dialogues on awareness, environmental preservation, and sustainable practices. In light of these activities, practical actions were developed such as the construction of models on: the pollution of the Arareau River, soil formation, soil types, a planned and tree-lined city, the water cycle, soil siltation, experimental practices such as: water treatment and filtration, cellulose production and consumption, cultural presentations such as: theater, recitations of cordel literature and poems, parodies, choir and musical performances. The pedagogical practice during the knowledge fair proved successful, especially due to the space given to students to be protagonists of their learning.DOI: https://doi.org/10.56238/edimpacto2025.092-014